2011
DOI: 10.1002/dvdy.22567
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic smad‐mediated BMP signaling revealed through transgenic zebrafish

Abstract: BMP signaling is fundamental to development, injury response, and homeostasis. We have developed transgenic zebrafish that report Smad-mediated BMP signaling in embryos and adults. These lines express either eGFP, destabilized eGFP, or destabilized KO2 under the wellcharacterized 'BMP Response Element' (BRE). These fluorescent proteins were found to be expressed dynamically in regions of known BMP signaling including the developing tailbud, hematopoietic lineage, dorsal eye, brain structures, heart, jaw, fins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 41 publications
2
112
0
2
Order By: Relevance
“…For example, the intracellular transducer of BMP signaling is nuclear pSmad1/5, which can be directly visualized by immunofluorescence [129,139,244,245]. There are also various transgenic reporters in zebrafish for Wnt [221,246,247], FGF [248], Nodal [83], RA [99,249], and BMP signaling [144,250252]. These reporter transgenes utilize sequences from a promoter that responds to the morphogen signal to drive reporter expression e.g.…”
Section: Current and Emergent Methods Of Spatial And Temporal Manimentioning
confidence: 99%
“…For example, the intracellular transducer of BMP signaling is nuclear pSmad1/5, which can be directly visualized by immunofluorescence [129,139,244,245]. There are also various transgenic reporters in zebrafish for Wnt [221,246,247], FGF [248], Nodal [83], RA [99,249], and BMP signaling [144,250252]. These reporter transgenes utilize sequences from a promoter that responds to the morphogen signal to drive reporter expression e.g.…”
Section: Current and Emergent Methods Of Spatial And Temporal Manimentioning
confidence: 99%
“…Previous work, using EGFP driven by a BRE, showed that both the endoderm and CNCCs are Bmp responsive during pharyngeal arch development . Our approach utilizing a BRE driving a destabilized form of GFP (Collery and Link, 2011) demonstrated that the endoderm and CNCCs receive Bmp signaling during different time windows, with the endoderm being Bmp responsive prior to the CNCCs. This Bmp response is highly dynamic, occurring in the prepouch endoderm and being rapidly downregulated in mature pouches.…”
Section: Bmp Signaling Regulates Endoderm and Craniofacial Developmentmentioning
confidence: 99%
“…To characterize the temporal and spatial dynamics of Bmp signaling in the pharyngeal arches, we utilized a destabilized form of GFP driven by a BRE derived from the mouse Id1 promoter, BRE:d2GFP (Collery and Link, 2011). Using double-transgenic embryos labeling the endoderm (sox17:dsRed) and Bmp-responsive cells (BRE:d2GFP) we found that the endoderm received canonical Bmp signaling as early as 14 hours post-fertilization (hpf) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To test whether, in kny/gpc4 mutants, the ectopic BMP activation observed at 20 hpf could be the consequence of enhanced canonical Wnt signaling, we crossed the Tg(hsp70:wnt8a-gfp) line with a BMP reporter line expressing an orange fluorescent protein, Tg(bre:dmKO2), and heat-shocked embryos at 16 hpf (Collery and Link, 2011). In contrast to later stages of heart development, we did not detect enhanced bre:dmKO2 activity in the cardiac disk or LPM of heat-shocked wnt8-gfp embryos (supplementary material Fig.…”
Section: Loss Of Knypek/glypican4 Results In Reduced Cardiomyocyte Numentioning
confidence: 99%